2020
DOI: 10.3389/fcell.2020.00782
|View full text |Cite|
|
Sign up to set email alerts
|

Roles of N6-Methyladenosine (m6A) in Stem Cell Fate Decisions and Early Embryonic Development in Mammals

Abstract: N6-methyladenosine (m 6 A) is one of the most abundant internal mRNA modifications, and it affects multiple biological processes related to eukaryotic mRNA. The majority of m 6 A sites are located in stop codons and 3 UTR regions of mRNAs. m 6 A regulates RNA metabolism, including alternative splicing (AS), alternative polyadenylation (APA), mRNA export, decay, stabilization, and translation. The m 6 A metabolic pathway is regulated by a series of m 6 A writers, erasers and readers. Recent studies indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 126 publications
(246 reference statements)
3
58
0
Order By: Relevance
“…This decrease was reversed by blocking FTO overexpression in the cultured spinal neurons co-transduced with AAV5- Fto shRNA ( Figure 6I ). Given the role of m 6 A modification in mRNA translation ( Jia et al, 2019 ; Zhang M. et al, 2020 ; Zhang Z. et al, 2020 ; Liu et al, 2020 ; Song et al, 2020 ), the evidence described above indicates that FTO likely erased the m 6 A enrichment in Mmp24 mRNA to promote the translation of Mmp24 mRNA in the spinal cord neurons under neuropathic pain condition.…”
Section: Resultsmentioning
confidence: 99%
“…This decrease was reversed by blocking FTO overexpression in the cultured spinal neurons co-transduced with AAV5- Fto shRNA ( Figure 6I ). Given the role of m 6 A modification in mRNA translation ( Jia et al, 2019 ; Zhang M. et al, 2020 ; Zhang Z. et al, 2020 ; Liu et al, 2020 ; Song et al, 2020 ), the evidence described above indicates that FTO likely erased the m 6 A enrichment in Mmp24 mRNA to promote the translation of Mmp24 mRNA in the spinal cord neurons under neuropathic pain condition.…”
Section: Resultsmentioning
confidence: 99%
“…Identifying factors involved in the osteogenic differentiation of ASCs is important for better understanding the mechanism of osteogenic differentiation. Recent studies have shown that m 6 A modification plays essential roles in stem cell fate decisions in a stage-, state-, and cell type-specific manner [ 26 , 36 40 ]. In the case of osteogenic differentiation, reduced m 6 A level in BMSCs inhibited osteogenic differentiation by affecting the PTH/Pth1r signaling axis, the PI3K-AKT signaling pathways, or the alternative splicing of VEGFA [ 30 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of RNA modifications in the context of developmental and neurological disorders remains an active area of study. m 6 A has been previously found to play important roles in embryonic development and neurobiological functions [ 84 , 85 ]. The roles of m 6 A and other RNA modifications in mediating neurologic function are further discussed elsewhere [ 84 , 86 , 87 , 88 , 89 ].…”
Section: Rna Modifications In Diseasesmentioning
confidence: 99%